From Concept to Community: Phased Modularity in a Participatory Public Space Design - Redyantanu, Bramasta Putra; Budhiyanto, Aris; Hariyanto, Agus Dwi (UI Scholars Hub, 2025)
This paper examines the idea of modularity as an extensive framework within the participatory design approach. Modularity is explored not only as a design and construction method but also as a collaboration framework that allows architecture to evolve through collaboration. In exploring the idea, this paper elaborates modularity through a community service design project at Alun-Alun Cemara Miagan, an open space in Miagan Mojoagung, Indonesia, emphasizing a participatory approach that involved local stakeholders and architects in developing a multifunctional public space. Due to the phased funding from the government, the project adopted modular strategies to enable flexible, incremental development aligned with community input. Three modular prototypes were developed: a gate responding to budget and fabrication constraints; a canopy providing adaptable shaded areas; and a building offering spatial flexibility for public functions. Through collaborative ideation in the participatory process, the hands-on engagement and iterative refinement from the community directly informed these design outcomes. This study demonstrates that modularity also supported local industries and addressed funding rhythms, demonstrating its value in both technical and social dimensions. The study also concludes that modular design can foster resilient, adaptable, and resource-efficient public spaces. It contributes to the discourse on community-based architecture and suggests future exploration of digital tools to enhance participatory modular development.